THE ḤAṬṬĀ'T: A RITE OF PASSAGE? - Milgrom, Jacob (Revue biblique, 1991)
A. Marx's proposal that the ḥaṭṭā't offerings separates its offerer from his sins must be rejected on philological and contextual grounds. The root meaning of ḥaṭṭā't and its application in the consecration rites of the Lévites, priest and altar wherein its blood is daubed not on the offerer but on the altar, imply that the altar is thereby purified, on essential first step in the rites of consecration. La proposition d'Alfred Marx, que les offrandes ḥaṭṭā'at séparent le donateur de ses péchés, doit être écartée sur des bases philologiques et contextuelles. Le sens de la racine, pour ḥaṭṭā'at , et son utilisation dans les rites de consécration des Lévites, du prêtre et de l'autel, rites dans lesquels le sang est appliqué non sur le donateur, mais sur l'autel, taut cela implique que l'autel est de ce fait purifié, une première étape essentielle dans les rites de consécration.